PEMBELAJARAN MENULIS TANGGAPAN TERHADAP BUKU FIKSI KELAS VIII SMP NEGERI 6 PONTIANAK - Puspitasari, Diah Ajeng; Syambasril, Syambasril; Muzzamil, Ahmad Rabbiul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractSMPN 6 Pontianak has recently implemented the 2013 Curriculum. This research discussed the planning, implementation, and evaluation in implementing the curriculum in the Indonesian language subject. This study aims to describe learning to write responses to fiction books based on the 2013 curriculum in class VIII students of SMP Negeri 6 Pontianak. The research method used is descriptive in the form of qualitative research. The data sources in this study were teachers and students. The theory used as the reference in this study is the theory of Indonesian language learning based on the 2013 curriculum. Based on the findings, it was concluded that (1) the first and second lesson plans designed by the teacher were in accordance with the 2013 curriculum, (2) the implementation of learning fiction and nonfiction books conducted by teachers based on Teacher Ability Assessment Tool 2 (APKG 2) has been implemented well, and (3) assessment of the learning of fiction and nonfiction books conducted by the teacher is in accordance with the assessment provisions based on the 2013 curriculum. Keywords: Learning Instruction, Writing Responses, Fiction Books